Apolipoprotein A-I mimetic peptide inhibits atherosclerosis by increasing tetrahydrobiopterin via regulation of GTP-cyclohydrolase 1 and reducing uncoupled endothelial nitric oxide synthase activity. (July 2021) - Ning, Da-Sheng; Ma, Jian; Peng, Yue-Ming; Li, Yan; Chen, Ya-Ting; Li, Shang-Xuan; Liu, Zui; Li, Yu-Quan; Zhang, Yi-Xin; Jian, Yu-Peng; Ou, Zhi-Jun; Ou, Jing-Song
Abstract: Background and aims: The apolipoprotein A-I mimetic peptide D-4F, among its anti-atherosclerotic effects, improves vasodilation through mechanisms not fully elucidated yet. Methods: Low-density lipoprotein (LDL) receptor null ( LDLr −/− ) mice were fed Western diet with or without D-4F. We then measured atherosclerotic lesion formation, endothelial nitric oxide synthase (eNOS) phosphorylation and its association with heat shock protein 90 (HSP90), nitric oxide (NO) and superoxide anion (O2 - ) production, and tetrahydrobiopterin (BH4) and GTP-cyclohydrolase 1 (GCH-1) concentration in the aorta. Human umbilical vein endothelial cells (HUVECs) and aortas were treated with oxidized LDL (oxLDL) with or without D-4F; subsequently, BH4 and GCH-1 concentration, NO and O2 - production, eNOS association with HSP90, and endothelium-dependent vasodilation were measured. Results: Unexpectedly, eNOS phosphorylation, eNOS-HSP90 association, and O2 - production were increased, whereas BH4 and GCH-1 concentration and NO production were reduced in atherosclerosis. D-4F significantly inhibited atherosclerosis, eNOS phosphorylation, eNOS-HSP90 association, and O2 - generation but increased NO production and BH4 and GCH-1 concentration. OxLDL reduced NO production and BH4 and GCH-1 concentration but enhanced O2 - generation and eNOS association with HSP90, and impaired endothelium-dependent vasodilation. D-4F inhibited the overall effects of oxLDL. Conclusions: Hypercholesterolemia enhanced uncoupled eNOS activity by decreasing GCH-1 concentration, thereby reducing BH4 levels. D-4F reduced uncoupled eNOS activity by increasing BH4 levels through GCH-1 expression and decreasing eNOS phosphorylation and eNOS-HSP90 association. Our findings elucidate a novel mechanism by which hypercholesterolemia induces atherosclerosis and D-4F inhibits it, providing a potential therapeutic approach. Graphical abstract: Image 1 Highlights: HSP90-eNOS association in absence of sufficient BH4 is pro-atherosclerotic. D-4F reduces HSP90-eNOS association to alleviate atherosclerosis. D-4F increases BH4 level by regulating GCH-1 expression in the aorta. D-4F maintains eNOS coupling by enhancing BH4 levels to inhibit atherosclerosis.